2020
DOI: 10.1523/jneurosci.0993-19.2019
|View full text |Cite
|
Sign up to set email alerts
|

Microglia Actively Remodel Adult Hippocampal Neurogenesis through the Phagocytosis Secretome

Abstract: During adult hippocampal neurogenesis, most newborn cells undergo apoptosis and are rapidly phagocytosed by resident microglia to prevent the spillover of intracellular contents. Here, we propose that phagocytosis is not merely passive corpse removal but has an active role in maintaining neurogenesis. First, we found that neurogenesis was disrupted in male and female mice chronically deficient for two phagocytosis pathways: the purinergic receptor P2Y12, and the tyrosine kinases of the TAM family Mer tyrosine … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
195
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 232 publications
(225 citation statements)
references
References 73 publications
(111 reference statements)
6
195
1
1
Order By: Relevance
“…Along these lines, monocyte-derived microglia-like cells from individuals with schizophrenia exhibit increased synapse engulfment 56 . Expression of P2Y 12 in microglia is important for synaptic plasticity 57 and for adult hippocampal neurogenesis 58 , which has been associated with the response to antidepressant treatment 59 . Neuronal activity regulates the surveilling function of microglia processes in the cortex via the monoamine neurotransmitter norepinephrine 60 , 61 , which is reduced in the brains of patients with depression 62 , 63 .…”
Section: Discussionmentioning
confidence: 99%
“…Along these lines, monocyte-derived microglia-like cells from individuals with schizophrenia exhibit increased synapse engulfment 56 . Expression of P2Y 12 in microglia is important for synaptic plasticity 57 and for adult hippocampal neurogenesis 58 , which has been associated with the response to antidepressant treatment 59 . Neuronal activity regulates the surveilling function of microglia processes in the cortex via the monoamine neurotransmitter norepinephrine 60 , 61 , which is reduced in the brains of patients with depression 62 , 63 .…”
Section: Discussionmentioning
confidence: 99%
“…Significantly, knockdown of microglial IL4Rα decreased the number of Arg1 + microglia and abrogated the antidepressant effects of IL4 overexpression, suggesting that IL4-driven Arg1 + microglia play a key role in protecting from CMS-induced depression-like behaviors. 26 Microglia constitute a prominent cell population within the hippocampal neurogenic niche 44 . Our results confirmed that CMS resulted in pro-inflammatory activation of microglia and inhibition of hippocampal neurogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…IL4-activated microglial cells promote oligodendrogenesis, whereas IFNγ-activated microglial cells stimulate neurogenesis [156]. Recent evidence shows that phagocytic microglia do not only play a role in passive clearance of apoptotic cells, but also play a central role in controlling adult hippocampal neurogenesis [157]. Chronic depletion of the purinergic receptor P2Y12 and the tyrosine kinases of the TAM family Mer tyrosine kinase (MertK)/Axl in mice impairs adult hippocampal neurogenesis, while the conditional reduced expression of MertK expression transiently increases adult hippocampal neurogenesis [157].…”
Section: Physiological Regulation Of Neurogenesis By Microgliamentioning
confidence: 99%